Beyond interactive and immersive media arts : a case study of teamLab in the construction of artificial nature - Li, Yihan (Nanyang Technological University, 2020)
Exploration of nature in art has seen endless forms and expressions and remains a great source of inspiration for global artists. Since the end of WWII, technological advancement has enabled many artists to start working with tools that differentiate their work from the traditional artistic creations of nature, such as landscape paintings or the land art movement. The result is the creation of highly immersive and interactive nature-like environments for visitors to experience, rather than appreciating them from a distance. Among these artists, teamLab - a Japanese creative group that brings artists, programmers, animators, and many other specialists under one roof - further developed such environments, creating many impactful and commercially successful projects globally. By situating and analysing the creation of teamLab among other nature-inspired works since 1960, and considering how total immersion, visitor engagement and participation are incorporated in these artificial nature, the research seeks to discover the special ingredient – the key aesthetics - that sets these projects apart from the previous ones. It also intends to establish a deeper understanding of nature in our current times.